Porovnanie ekonomickeho rozvoja Slovenskej republiky a Českej republiky na základe indexu globalnej kkonkurencieschopnosti - Bondareva, Irina; Tomčík, Róbert (Univerzita Pardubice, 2015)
The aim of this article is to analyze the competitiveness of the Slovak Republic expressed by the Global Competitiveness Index and compare its value with Czech Republic. The Czech Republic was chosen as a basis of comparison because of the similarity of its economy with the Slovak Republic. This article describes the methodology for assessing the competitiveness of countries according to the World Economic Forum. This article also describes pillars of competitiveness, which consist of the key factors affecting the competitiveness of any country. Classification of countries assessed into three main groups according to the sophistication of the economy can detect those factors that affect the level of competitiveness of the selected country the most. By analysis of the various pillars is also possible to recognize problematic factors, i.e. those pillars characterized by low values in the long period, which need attention. The article describes the most problematic areas of competitiveness of the Slovak Republic. These include mainly the low quality of public institutions, a significant level of corruption in the country and as another problematic factor is considered a low innovation activity of the country.
Comparison of economic development of the Slovak Republic and the Czech Republic based Global Competitiveness Index
Keywords: competitiveness; Global Competitiveness Index; corruption; innovation; institutions; O11; O47